Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1590/s1677-5538.ibju.2013.02.17
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor mediates activation of microglial cells in prostate of chemically irritated rats

Abstract: Purpose: Evidence shows that adenosine triphosphate (ATP) is involved in the transmission of multiple chronic pain via P 2 X 7 receptor. This study was to investigate the P 2 X 7 and microglial cells in the chronic prostatitis pain. Materials and Methods: Rats were divided into control group and chronic prostatitis group (n = 24 per group). A chronic prostatitis animal model was established by injecting complete Freund's adjuvant (CFA) to the prostate of rats, and the thermal withdrawal latency (TWL) was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…3 , 144 , 145 Spinal microglia been found to contribute to pain in male animals with chronic prostatitis. 146 , 147 To our knowledge, however, there are currently no comprehensive studies investigating glial contributions to pain associated with visceral diseases that have been restricted to, or with a substantial focus on, females. This alternative scope in research could reveal distinct female pain mechanisms that may be exploited to improve pain management.…”
Section: Neuroimmune Contributions To the Female Predominance Of Painmentioning
confidence: 99%
“…3 , 144 , 145 Spinal microglia been found to contribute to pain in male animals with chronic prostatitis. 146 , 147 To our knowledge, however, there are currently no comprehensive studies investigating glial contributions to pain associated with visceral diseases that have been restricted to, or with a substantial focus on, females. This alternative scope in research could reveal distinct female pain mechanisms that may be exploited to improve pain management.…”
Section: Neuroimmune Contributions To the Female Predominance Of Painmentioning
confidence: 99%
“…After stimulating the bladder and prostate with acetic acid or formalin, the number of c-fos-positive cells in the lumbosacral spinal cord was significantly increased [10], indicating that the lumbosacral spinal cord is involved in the neural circuit of prostate pain. Furthermore, immunohistochemistry and pharmacological blockade experiments have also illustrated that CP/CPPS can activate microglia in the rat L5-S2 spinal cord through the P2X7 receptor [11, 12] and that inhibition of microglia activation can alleviate persistent prostate pain [11]. There is increasing evidence that spinal microglia and astrocytes play important roles in chronic pain sensitization by releasing cellular mediators such as cytokines, chemokines, and growth factors [1315].…”
Section: Introductionmentioning
confidence: 99%
“…And Hua et al found that CXCL10 was an important molecule involved in inflammatory infiltration and pain symptoms of prostatitis by promoting the migration of macrophages and secretion of inflammatory mediators via CXCR3‐mediated ERK and p38 mitogen‐activated protein kinase (MAPK) activation [ 43 ] . Similarly, microglia, resident immune cells of the central nervous system which have the phenotypic similarity of microglia to peripheral blood monocytes/macrophages and dendritic cells [ 44 ] , were also found abnormally activated and correlated with pain and depressive symptoms as well as cognitive impairment of EAP animals [ 45–48 ] .…”
Section: Resultsmentioning
confidence: 99%